Penerapan Budidaya Microgreen sebagai Inovasi Pertanian Berkelanjutan di Kelompok Tani Hasanah - sohriati, eva; Rahmawati, Hilda; Muhajirah Yunus, Nur (Jurnal Biogenerasi, 2025)
Microgreens are young vegetable plants harvested 7–14 days after planting. They boast high nutritional content and have growing market potential in line with public awareness of a healthy lifestyle. This study aims to assess the application of microgreen cultivation in the Hasanah Farmers Group as an effort to diversify their farming business and increase farmer income. The research was conducted using a participatory Rural Appraisal (PRA) approach, involving farmer group members at every stage, from media preparation, planting, maintenance, harvesting, and marketing. The results indicate that microgreen cultivation can be carried out using simple technology, at low cost, while generating significant added value. Tray microgreen harvests yield an average of 250–300 grams per cycle with a selling price of IDR 20,000–25,000 per 100 grams. The profit margin for microgreen farming in the Hasanah Farmers Group reaches 45–55% compared to production costs. In conclusion, microgreens have the potential to become a promising alternative commodity to improve farmer welfare through a modern, sustainable agricultural system